Determination Of The Judges Freedom In Indonesia On The Straf Minimum Rules - IMRAN, Suwitno Y; APRIPARI, Apripari (Indonesia Strategic Sustainability, 2022)
Limiting the freedom of judges in expressing legal logics in each particular case will only hinder the process of seeking true values of justice. This freedom does not mean being free without being accompanied by legal responsibilities. the philosophical aspect of the principle of freedom of judges, and the ideal model for the application of the principle of freedom of judges in Indonesia in the minimum rules straf system, is the subject that will be discussed in this article. The normative research method used in this article uses a statutory, historical and conceptual approach and uses primary and secondary legal materials that are presented descriptively. The conclusion obtained confirms that the aspect of judges' freedom philosophically in principle begins with the application of the division of powers namely, legislative, executive and judicial which is the philosophical basis that the judicial branch of power is an independent branch of power and judges have the freedom to make interpretations, legal findings based on the conscience and conviction of the judge. As for the straf minimum rules case, the ideal model for implementing the principle of judge freedom can be realized through the theory of balance, namely that judges in deciding cases are not based on the context of laws and regulations and must consider aspects of the judge's belief even though the decision is contrary to the law, but as long as it is related to the judge's belief, then it can be justified on the basis of the judge's freedom.